The healthcare professionals’ role in older adults’ road safety in primary care settings in Canada: a qualitative study - Camille Savoie; Philippe Voyer; Suzanne Bouchard; Martin Lavallière (BMC Health Services Research)
Abstract Background During the aging process, many older adults will see their ability to drive affected, particularly due to the high prevalence of health problems. To this end, healthcare professionals working in primary care are in frequent contact with older drivers at risk and for whom interventions must be undertaken. However, little is known about their role, despite the major implications with legal authorities in assessing fitness to drive and in reporting unsafe drivers, especially in a Quebec setting. The purpose of this study was to describe the role of primary healthcare professionals in road safety. Methods Within a descriptive qualitative design, semi-structured interviews were undertaken with 27 primary healthcare professionals (registered nurses (n = 16), occupational therapists (n = 7), and family physicians (n = 4)). Using an inductive approach, qualitative data was analyzed with the content analysis method. Results The road safety role of the primary healthcare professionals interviewed varied between professions, depending on their respective expertise. Furthermore, they work in close collaboration and interdisciplinarity. Their role is divided into two main components, namely screening and assessment of older drivers’ driving abilities, as well as of the support and accompaniment offered to older adults, following the loss of their driver’s license. Their role also differs in terms of legally declaring older drivers fit or not to drive. Some professionals integrate preventive interventions into their practice, aimed either to keep older adults driving as long as possible, or to prepare them to stop driving. Several healthcare professionals reported experiencing challenges, especially during the process of assessing their older patients’ fitness to drive. Conclusions This study’s results will help organizations to develop training programs allowing primary healthcare professionals to improve their practice with older drivers and their loved ones.